Towards Profiling of the G-Quadruplex Targeting Drugs in the Living Human Cells Using NMR Spectroscopy - Krafčík, Daniel; Ištvánková, Eva; Džatko, Šimon; Víšková, Pavlína; Foldynová-Trantírková, Silvie; Trantírek, Lukáš (International journal of molecular sciences, 2021)
Recently, the 1H-detected in-cell NMR spectroscopy has emerged as a unique tool allowing the characterization of interactions between nucleic acid-based targets and drug-like molecules in living human cells. Here, we assess the application potential of 1H and 19F-detected in-cell NMR spectroscopy to profile drugs/ligands targeting DNA G-quadruplexes, arguably the most studied class of anti-cancer drugs targeting nucleic acids. We show that the extension of the original in-cell NMR approach is not straightforward. The severe signal broadening and overlap of 1H in-cell NMR spectra of polymorphic G-quadruplexes and their complexes complicate their quantitative interpretation. Nevertheless, the 1H in-cell NMR can be used to identify drugs that, despite strong interaction in vitro, lose their ability to bind G-quadruplexes in the native environment. The in-cell NMR approach is adjusted to a recently developed 3,5-bis(trifluoromethyl)phenyl probe to monitor the intracellular interaction with ligands using 19F-detected in-cell NMR. The probe allows dissecting polymorphic mixture in terms of number and relative populations of individual G-quadruplex species, including ligand-bound and unbound forms in vitro and in cellulo. Despite the probe's discussed limitations, the 19F-detected in-cell NMR appears to be a promising strategy to profile G-quadruplex-ligand interactions in the complex environment of living cells.
Keywords: BRACO19; protony; vazebná místa; KRAS; DNA; lidé; Nucleic Acid Conformation; telomeric DNA; Pharmaceutical Preparations; léčivé přípravky; Ligands; konformace nukleové kyseliny; Models, Molecular; G-kvadruplexy; magnetická rezonanční spektroskopie; G-Quadruplexes; drug; molekulární modely; NMM; in-cell NMR; G-quadruplex; ligand; Protons; Bcl2; Magnetic Resonance Spectroscopy; PhenDC3; ligandy; Binding Sites; Humans